The role of system Xc− in methamphetamine-induced dopaminergic neurotoxicity in mice. (September 2017) - Dang, Duy-Khanh; Shin, Eun-Joo; Tran, Hai-Quyen; Kim, Dae-Joong; Jeong, Ji Hoon; Jang, Choon-Gon; Nah, Seung-Yeol; Sato, Hideyo; Nabeshima, Toshitaka; Yoneda, Yukio; Kim, Hyoung-Chun
Abstract: The cystine/glutamate antiporter (system Xc −, Sxc) transports cystine into cell in exchange for glutamate. Since xCT is a specific subunit of Sxc, we employed xCT knockout mice and investigated whether this antiporter affected methamphetamine (MA)-induced dopaminergic neurotoxicity. MA treatment significantly increased striatal oxidative burdens in wild type mice. xCT inhibitor [i.e., S-4-carboxy-phenylglycine (CPG), sulfasalazine] or an xCT knockout significantly protected against these oxidative burdens. MA-induced increases in Iba-1 expression and Iba-1-labeled microglial immunoreactivity (Iba-1-IR) were significantly attenuated by CPG or sulfasalazine administration or xCT knockout. CPG or sulfasalazine significantly attenuated MA-induced TUNEL-positive cell populations in the striatum of Taconic ICR mice. The decrease in excitatory amino acid transporter-2 (or glutamate transporter-1) expression and increase in glutamate release were attenuated by CPG, sulfasalazine or xCT knockout. In addition, CPG, sulfasalazine or xCT knockout significantly protected against dopaminergic loss (i.e., decreases in tyrosine hydroxylase expression and immunoreactivity, and an increase in dopamine turnover rate) induced by MA. However, CPG, sulfasalazine or xCT knockout did not significantly affect the impaired glutathione system [i.e., decrease in reduced glutathione (GSH) and increase in oxidized glutathione (GSSG)] induced by MA. Our results suggest that Sxc mediates MA-induced neurotoxicity via facilitating oxidative stress, microgliosis, proapoptosis, and glutamate-related toxicity. Highlights: Genetic or pharmacologic inhibition of xCT exhibits protective potentials against MA. xCT inhibition exerts antioxidant and antiapoptotic effects against MA neurotoxicity. xCT inhibition attenuates microglial activation and glutamate toxicity induced by MA. xCT inhibition does not affect glutathione system impairment induced by MA.